The study of use of toluidine blue as an adjunctive tool to clinical examination in early diagnosis of clinically suspicious oral premalignant and malignant lesions: a study of fifty cases - Bayad, Himanshu Chhagan; Bhagat, Sanjeev; Sahni, Dimple; Kaur, Navneet; Singh, Ravinder; Sharma, Dinesh Kumar; Singh, Baldev (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Oral carcinoma is among the most prevalent malignancies of head and neck region and is often diagnosed in the advanced stage with significant morbidity and treatment cost. Thus, there is a need for early detection of oral premalignant and malignant lesions. Toluidine blue staining can be used for early detection of these lesions. Methods: The study included 50 patients with clinically suspicious oral premalignant and malignant lesions. These lesions were subjected to toluidine blue staining and biopsy. Diagnoses were confirmed by histopathological examination. Results: Sensitivity and specificity of toluidine blue for oral premalignant lesions was 92.30% and 80% respectively with the positive predictive value of 92.30%, negative predictive value of 80% and accuracy of 88.88%. Sensitivity and specificity of toluidine blue for oral malignant lesions was 96.30% and 80% respectively with the positive predictive value of 96.30%, negative predictive value of 80% and accuracy of 93.75%. Conclusions: The simplicity of toluidine blue staining and its accuracy suggest that it can be a useful adjunctive tool to diagnosis of oral lesions. Results should be carefully evaluated and correlated with clinical findings and histopathological diagnosis.